2016
DOI: 10.1016/j.jtcvs.2015.08.120
|View full text |Cite
|
Sign up to set email alerts
|

Transesophageal versus transcranial motor evoked potentials to monitor spinal cord ischemia

Abstract: Transesophageal motor evoked potentials may be superior to transcranial motor evoked potentials in terms of quicker response to spinal cord ischemia and better prognostic value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…In previous animal studies, histologic changes were generally observed 48 h after induction of cord infarction. Profound gray matter (GM) and white matter (WM) injuries accompanied by neuronal cell damage and a decline in cell numbers were observed, and the boundary between the two areas also became steadily unclear (24,25). The abnormal spinal cord conduction velocity findings may be primarily related to WM injuries accompanied by myelinated axonal damage, which is known to be eventually correlated with the extent of GM injuries (26,27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous animal studies, histologic changes were generally observed 48 h after induction of cord infarction. Profound gray matter (GM) and white matter (WM) injuries accompanied by neuronal cell damage and a decline in cell numbers were observed, and the boundary between the two areas also became steadily unclear (24,25). The abnormal spinal cord conduction velocity findings may be primarily related to WM injuries accompanied by myelinated axonal damage, which is known to be eventually correlated with the extent of GM injuries (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies have also demonstrated that MEP responses to ischemia are sensitive and immediate. Tsuda et al (25) induced spinal infarction in dogs using aortic balloon occlusion and checked for changes in MEP. They discovered that transcranial MEP amplitude reduced by 50% in about 6 min, and completely disappeared in around 7 min.…”
Section: Discussionmentioning
confidence: 99%
“…Anesthesia and instrumentation procedures were performed according to previously reported methods. 14 , 15 Briefly, the animals were anesthetized with intravenous infusion of propofol (12-24 mg/kg/h) and remifentanil (12-24 μg/kg/h) and were maintained on mechanical ventilation. For MEP recording, a Neuropak MEB-2200 system (Nihon Kohden, Tokyo, Japan) was used for data acquisition, processing, and analysis, with SEN-4100 equipment for electrical stimulation (Nihon Kohden, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown that transesophageal MEP (TE-MEP), which we call monopolar TE-MEP (monoTE-MEP) in this study, is feasible, safe, and superior to TC-MEP in terms of stability, response time to ischemia/reperfusion, and prognostic value in canine experiments. 14 , 15 We think that it is because supramaximal intensity stimulation can be applied safely and easily to the spinal cord. However, cervical cord stimulation results in the direct stimulation of the cervical alpha motor neurons with strenuous forelimb movement, which may be dangerous in clinical settings, and precludes forelimb potentials to be used as a real-time control.…”
mentioning
confidence: 99%
“…These authors previously showed in canine experiments that measurement of monopolar transesophageal motor-evoked potentials (m-TE-MEP) is feasible, safe, and superior to TC-MEP in terms of stability, response time to ischemia/reperfusion, and prognostic value. 8 They induced SCI by aortic balloon occlusion at the thoracic level for 10 minutes and evaluated response time at the proximal thoracic cord after 25 minutes. Interestingly, bipolar transesophageal (bi-TE) stimulation was successful in all animals, and their forelimb waveforms were identical to those obtained with transcranial stimulation.…”
mentioning
confidence: 99%